Thermal Degradation of Type I Collagen from Bones - Lambri, Osvaldo Agustin F. (2016)
The denaturation processes of collagen in the temperature range between 450 K and 670 K are revealed through studies performed on cow rib bones by means of mechanical spectroscopy, differential scanning calorimetry, thermogravimetry, scanning electron microscopy and infrared spectroscopy. The conformational change of the collagen molecules from a triple helix structure to a random coil was found at around 510 K. It was determined that the transformation is developed through the viscous movement of fibrils with an activation energy of (127 ± 8) kJ/mol. The second stage of massive bulk deterioration of the collagen was found at around 600 K, which leads to the loss of the mechanical integrity of the bulk collagen. In addition, an easy-to-handle viscoelastic procedure for obtaining the activation energy of the denaturation process from mechanical spectroscopy studies was also shown.